O laboratório de ensino de matemática e a identificação de obstáculos no conhecimento de professores de matemática - Barroso, Mariana Moran (2010)
To accomplish this task we researched the foundation and importance of the Laboratory for Teaching Mathematics (LTM); when mathematics professors work with the contents of this subject in a laboratory environment. The objective was to incite a revision of a sediment mathematical concept, to be detected in the environment of LTM, if there are obstacles in solving issues in the mathematical skills of mathematics professors. The survey was conducted in the Laboratory for Teaching Mathematics (LTM), for duration of 64 hours, with the participation of 60 mathematics professors of the Regional Teaching Center of Maringá. Theoretically we have a fundamental notion of obstacles in the theory of knowledge and data. The research was divided into the following categories: exploratory, data collection, analysis, hypotheses formulation and observation. We researched how much knowledge of LTM, the observed professors had and if the availability of games and manipulated materials helped in changing their conceptions on LTM. We also analyzed the contribution of LTM in the identification of epistemological obstacles in the know-how and data of the professors. Based on these issues, we see some positive changes related to pre-conceptions of the participating professors in regards to the Laboratory for Teaching Mathematics. We also found obstacles in the comprehension and data that misguided the professors' knowledge and prevented them from understanding the construction of certain mathematical concepts.